THE IMPACT OF ORTHOKERATOLOGIC CONTACT LENSES ON SPHERICAL ABERRATION OF THE OPTICAL SYSTEM OF THE EYE - E. P. Tarutta (Российский офтальмологический журнал, 2018)
The purpose of this study is to measure the spherical aberration (SA) of the cornea and the optical system of the eye before and after wearing orthokeratologic (OK) contact lenses. Material and methods. 22 patients (44 eyes) with myopia aged 11 to 18 years were examined. The total SA was determined after medical cycloplegia performed on OPD-Scan III aberrometer, Nidek. To analyze SA values before and after wearing OK lenses, we chose pupil areas from 3 mm to 7.5 mm in 0.5-1 mm increments. Results. In intact eyes with myopia, the total SA is mildly positive and is growing with the increase of the pupil diameter. After OK correction, the SA is changing: from 3 to 6 mm of the pupillary area, the positive SA increases by 50-130 %, in the 6.3 mm area it falls sharply and becomes negative, growing on the way to the periphery of the pupillary area. Conclusions. Corneal topography changes after OK corrections lead to specific changes of the wavefront of myopic eyes, causing increased visual performance and eliminating the hyperopic defocus at retinal periphery. For citation: Tarutta E.P., Harutyunyan S.G. The impact of orthokeratologic contact lenses on spherical aberration of the optical system of the eye. Russian ophthalmological journal. 2018; 11 (2): 17-21. doi: 10.21516/2072-0076-2018-11-2-17-21 (In Russian).